Gatekeeper Improves Voluntary Contractility in Patients With Fecal Incontinence. (June 2019) - Grossi, Ugo; De Simone, Veronica; Parello, Angelo; Litta, Francesco; Donisi, Lorenza; Di Tanna, Gian Luca; Goglia, Marta; Ratto, Carlo
Background . Gatekeeper (GK) has shown to be safe and effective in patients with fecal incontinence (FI). We aimed to understand its mechanism of action by comparing pre- and post-implant change in the external anal sphincter (EAS) contractility. Methods . Study of EAS contractility was conducted in 16 FI females (median age = 69 years) before and after implant of 6 GK prostheses. Muscle tension ( Tm ), expressed in millinewtons per centimeter squared, mN(cm 2 ) −1, was calculated using the equation Tm = P(ri )(tm) −1, where P is the average maximum squeeze pressure and ri and tm the inner radius and thickness of the EAS, respectively. The effect of a predefined set of covariates on Tm was tested by restricted maximum likelihood models. Results . Compared with baseline, despite unchanged tm (2.7 [2.5-2.8] vs 2.5 [2.2-2.8] mm; P = .31 mm), a significant increase in P (median = 45.8 [26.5-75.8] vs 60.4 [43.1-88.1] mm Hg; P = .017), and ri (12.4 [11.5-13.4] vs 18.7 [17.3-19.6] mm; P < .001) resulted in an increase in Tm (233.2 [123.8-303.2] vs 490.8 [286.9-562.4] mN(cm 2 ) −1 ; P < .001) at 12 months after GK implant. Twelve-month follow-up improvements were also observed on Cleveland Clinic FI score (8-point median decrease; P = .0001), St Marks FI score (10-point median decrease; P < .0001), and American Medical Systems score (39-point median decrease; P < .0001). Restricted maximum likelihood models showed that years of onset of FI was negatively associated with change in Tm ( P = .048). Conclusions . GK-related EAS compression positively influences muscle contractility by increasing ri, with consequent increase in Tm (length-tension relationship). Further studies are needed to confirm the long-term effectiveness of GK.